Hotline equipment / Abdul Halim Che Mud and Naser Ali - Che Mud, Abdul Halim; Ali, Naser (1993)
Intercom was introduced as a telecommunication system which does not use telephone exchanges. But it has drawbacks such as unusual ringing sound without ringing tone, shorter distance coverage and its main need to a key button to function. In our project, our objective was to design a hotline equipment to be used as a point-to-point communication independently from the telephone exchange but has the same features like the existing hotline service provided by Telekom Malaysia. Details of the design and technical description of our hotline equipment as well as the comparison with the existing hotline and intercom systems are discussed in this report.